User Expectations on Telemedicine Financing in the National Health Insurance Era - Rani Tiyas Budiyanti; Chriswardani Suryawati; Murni Murni; Matsna Hanifah (Jurnal Manajemen Kesehatan Indonesia, 2022)
Telemedicine users have increased during the Covid-19 pandemic. Telemedicine can provide alternative solutions to improving quality, and access, and reducing disparities in health services, especially in urban and remote areas. However, in the era of national health insurance, not all telemedicine is covered by Healthcare and Social Security Agency (BPJS Kesehatan). This study aims to determine user expectations of telemedicine financing in the national health insurance era. This research is quantitative research with a descriptive approach which was conducted in February-April 2022. The respondents were 102 people who had used telemedicine services in Indonesia that were selected through the quota sampling method. The results showed that 95.1% of respondents agreed that telemedicine services were covered by the National Health Insurance (NHI), either fully or by sharing costs. As many as 31.95% of respondents expect 25% of cost-sharing with NHI, 35.05% of respondents expect 50% of cost-sharing with NHI, 12.37% of respondents expect 80% of cost-sharing with NHI, and 20.63 % hope 100% will be covered by NHI. Further and specific regulation related to telemedicine is needed. The type of telemedicine service covered communication with the telemedicine service provider, and the amount of the service fee covered needs to be communicated between the relevant parties